Audience -Citizens: the media, public knowledge and Interpretive practice - Harindranath, Ramaswami (Sage Publications India, 2009)
udience–Citizens: The Media, Public Knowledge and Interpretive Practice explores the relationship between media and democracy from the perspective of the audience and proposes a unique conceptual framework for the analysis of audiences, consumption patterns and citizenship. Drawing on original research on the interpretation of documentaries by audiences in India and Britain, this book examines how sociological and cultural factors affect the interpretation of mediated knowledge. It develops a fresh approach to the relational dynamics of media and politics in contemporary India and by extension elsewhere in the developing world.